Characterisation of HIV-1 reservoirs in paediatric populations: protocol for a systematic review and meta-analysis - Francesca Ceccherini-Silberstein; Joseph Fokam; Vittorio Colizzi; Desire Takou; Carlo-Federico Perno; Georgia Ambada; Maria-Mercedes Santoro; Sharon R Lewin; Aude Christelle Ka’e; Aubin Nanfack; Bouba Yagai; Bertrand Sagnia; et al. (BMJ Open, 2023)
Introduction The success of antiretroviral therapy (ART) has changed HIV from a deadly to a chronic infection, thus increasing the transitioning from infancy toward adulthood. However, the virostatic nature of antiretrovirals maintains viruses in sanctuaries, with reactivation potentials. Because current ARTs are very limited for children, the emergence of new HIV epidemics driven by HIV drug-resistance mutations is favoured. Our systematic review aims to estimate the global burden of archived drug-resistance mutations (ADRMs) and the size of reservoir (HIV-1 DNA load), and their associated factors in children and adolescents.Methods and analysis Papers from the PubMed/MEDLINE, Google Scholar, ScienceDirect, African Journals Online and Academic Medical Education Databases will be systematically identified using the keywords: “HIV-1 reservoirs”, “viral reservoirs”, “HIV-1 DNA”, infants, adolescents, child and children, linked by the following Boolean operators: ‘OR’ and ‘AND’. Randomised and non-randomised trials, cohort studies and cross-sectional studies published in French or English from January 2002 will be included, while case reports, letters, comments, reviews, systematic reviews and meta-analyses, and editorials will be excluded. All studies describing data on ADRMs, HIV-1 DNA load and/or immunological markers among children/adolescents will be eligible. A random-effects model will be used to calculate the pooled prevalence of ADRMs. Data will be reported according to type of viral reservoir (peripheral blood mononuclear cells, CD4 cells), geographical location (country/continent), ethnicity/race, age (infants vs adolescents), gender, HIV-1 clades, ART exposure (naïve vs treated, drug class, type of regimen, age at ART initiation and treatment duration), WHO clinical staging (I, II, III, IV), immune status (immune compromised vs immune competent) and virological response (viraemic vs non-viraemic). Multivariate logistic regression will be performed to determine predictors of HIV reservoir profile in paediatric populations. The primary outcome will be to assess the genotypical and quantitative profile of HIV reservoirs, while the secondary outcomes will be to identify factors associated with ADRMs and reservoir size in paediatric populations.Ethics and dissemination Ethical approval is not applicable for this study as it will be based on published data. Results will be disseminated via a peer-reviewed scientific journal and relevant conferences.PROSPERO registration number CRD42022327625.